Rancangan VFR Corridor di Perum LPPNPI Kantor Cabang Aceh - Riska Ramadanty Imran; Rany Adiliawijaya Putriekapuja; Yudha Abimanyu (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
This research has purpose to knowing the problem will be unavailability VFR corridor for VFR flight in ATC service at Perum LPPNPI branch Aceh. Methode in this research using research and development level one with qualitative approaching and descriptive exposure. Collecting data using literature, documentation and interview. While, methode of data processing are using data reduction, presentation of data, conclusion and verification. Stand with data has collected, VFR flight has no route and it makes the ATC difficult to know the true position of the aircraft due to the route always different in every aircraft and as flow as pilot knowing. Therefore, VFR route draft as a solution.